2010
DOI: 10.1111/j.1582-4934.2010.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding protein Musashi1 regulates apoptosis, gene expression and stress granule formation in urothelial carcinoma cells

Abstract: The RNA-binding protein Musashi1 (MSI1) is a marker of progenitor cells in the nervous system functioning as a translational repressor. We detected MSI1 mRNA in several bladder carcinoma cell lines, but not in cultured normal uroepithelial cells, whereas the paralogous MSI2 gene was broadly expressed. Knockdown of MSI1 expression by siRNA induced apoptosis and a severe decline in cell numbers in 5637 bladder carcinoma cells. Microarray analysis of gene expression changes after MSI1 knockdown significantly up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…All these finding suggest that Msi1 function as an oncogene. This notion is further supported by the findings that ablation of Msi1 in gliomas (6) or bladder carcinoma cells (21) suppressed the cell cycle, and induced apoptosis and showed severe decline in cell numbers. However, Msi1 has also been proposed to have no significant effect on cell proliferation in human intestinal epithelial cells (22).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…All these finding suggest that Msi1 function as an oncogene. This notion is further supported by the findings that ablation of Msi1 in gliomas (6) or bladder carcinoma cells (21) suppressed the cell cycle, and induced apoptosis and showed severe decline in cell numbers. However, Msi1 has also been proposed to have no significant effect on cell proliferation in human intestinal epithelial cells (22).…”
Section: Introductionsupporting
confidence: 70%
“…In the present study, we also found that downregulation of Msi1 inhibited the cell cycle by blocking the G 1 /S transition in 2 colon cancer cell lines. Furthermore, we found that knockdown of Msi1 upregulated the expression of p21 the findings in bladder carcinoma (21) and breast cancer (19). p21 cip1 is a universal cyclin dependent kinase (CDK) inhibitor that directly inhibits the activity of cyclin-CDK complexes, resulting in cell cycle arrest at G 0 /G 1 phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression microarray analysis and evaluation were performed with independent triplicate RNA preparations from each cell line using HG U133A GeneChips (Affymetrix, Berlin, Germany) as described previously [26]. For functional annotation, the Database for Annotation, Visualization and Integrated Discovery (DAVID), version v6.7, was used [27].…”
Section: Microarray Gene Expression Profilingmentioning
confidence: 99%
“…The Notch receptor NOTCH1 and its ligand DLL1 are significantly down-regulated in urothelial carcinoma tissues Expression of several Notch pathway components was measured at the mRNA level by qRT-PCR in a wellcharacterized set of invasive urothelial carcinoma and normal bladder tissue samples that we had previously used for other studies [27]. Expression of NOTCH1 and NOTCH2 was significantly decreased in almost all urothelial cancers ( Figure 1A-B).…”
Section: Resultsmentioning
confidence: 99%